Stepping Ahead from Agency and Stewardship Theory: An Islamic Perspective - Puja Rizqy Ramadhan (International Journal of Religious and Cultural Studies, 2022)
This paper seeks to review the relevance of Agency Theory and Stewardship Theory in uncovering the reality of public sector organizations, where at the same time Islam as a source of value has a unique perspective in providing views and other possibilities on organizational behavior in the public sector. This paper uses a qualitative design with literature-review approach. Through an Islamic perspective, organizations are not seen only as a fulfillment of the economic desires of their actors as in Agency Theory, nor are they seen as a container of personal achievement as described in Stewardship Theory. Islam prioritizes the value of divinity and humanity as its foundation. This then has an impact on the attitude of the actors who are oriented towards providing the greatest benefit to fellow human beings so that in the end it will have positive implications in the context of society in general.